2008
DOI: 10.1089/end.2007.0442
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Retroperitoneal Lymph Node Dissection for Low-Stage Testicular Cancer

Abstract: Skolarus, T. A.; Bhayani, S. B.; Chang, H. C.; Brandes, S. B.; Kibel, A. S.; Landman, J.; and Figenshau, R. S., ,"Laparoscopic retroperitoneal lymph node dissection for low-stage testicular cancer." Journal of Endourology.22,7. 1485Endourology.22,7. -1490Endourology.22,7. . (2008 Results: A total of 26 L-RPLND procedures were completed, 3 for paratesticular rhabdomyosarcoma. Mean operative time was 250 minutes (range 176-369 min); estimated blood loss was 145 mL (range 50-500 mL); lymph node count was 23.8 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…In most contemporary series adjuvant chemotherapy continues to be given to patients with any nodal involvement at the time of LRPLND. Of the 122 node positive patients reported in the series listed in Table 1 following LRPLND [Skolarus et al 2008 [Steiner et al 2008]. None of the five patients were given adjuvant chemotherapy and all are without recurrence at follow-up intervals of 2-35 months.…”
Section: Lrplnd Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…In most contemporary series adjuvant chemotherapy continues to be given to patients with any nodal involvement at the time of LRPLND. Of the 122 node positive patients reported in the series listed in Table 1 following LRPLND [Skolarus et al 2008 [Steiner et al 2008]. None of the five patients were given adjuvant chemotherapy and all are without recurrence at follow-up intervals of 2-35 months.…”
Section: Lrplnd Techniquementioning
confidence: 99%
“…Postoperative complications have been reported at a rate of 9.4-25.7% in contemporary series [Cresswell et al 2008;Skolarus et al 2008;Neyer et al 2007;Nielsen et al 2007;Albqami and Janetschek, 2005]. Reported complications include chylous ascites, ileus, lymphocele, nerve injury, pulmonary embolus, C. difficile colitis, retroperitoneal hematoma and urinoma [Kenney and Tuerk, 2008].…”
Section: Complications Of Lrplndmentioning
confidence: 99%
See 1 more Smart Citation
“…4,21,22 Indeed, recent reports of long-term outcomes of L-RPLND indicate that oncologic efficacy in terms of disease-free and diseasespecific survival is equivalent to that of O-RPLND. 2,3,[5][6][7][8]10,23 In addition, high-volume centers report that, in experienced hands, L-RPLND is associated with less morbidity, shorter hospital stays, and fewer overall complications compared with O-RPLND, while demonstrating inferiority only in terms of increased operative time and slightly increased overall costs. 3,5,[8][9][10]21,[24][25][26] Furthermore, L-RPLND has been demonstrated to be associated with less bother from postoperative pain compared with O-RPLND, as well as faster return to normal daily activities and improved quality of life scores on validated questionnaires.…”
Section: Benway Et Almentioning
confidence: 99%
“…1 Recent reports, however, indicate that laparoscopic retroperitoneal lymph node dissection (L-RPLND) may be a viable alternative to the open approach. [2][3][4][5][6][7][8][9][10] One of the major concerns surrounding L-RPLND has been its adequacy as a stand-alone procedure that does not require the use of adjuvant chemotherapy in the instance of incomplete dissection. 11,12 Indeed, while initial long-term studies have demonstrated oncologic outcomes equivalent to an open approach, 2,3,5,8,10 there is a paucity of literature directly comparing the lymph node yield between L-RPLND and O-RPLND, with one recent direct comparison suggesting that node counts are significantly less with the laparoscopic approach, 9 while another meta-analysis suggests that node counts may be the same between the two approaches at highvolume centers.…”
mentioning
confidence: 99%